Analisis Pengaruh Financial Technology, Financial Literacy, Financial Knowledge, Locus of Control, dan Income terhadap Perilaku Keuangan - Ani Wiranti (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
As a developing country, Indonesia is quite good at following the development of financial technology in the world. The global fintech industry continues to grow significantly even in the pandemic era because people must carry out all activities at home, including financial transactions that are currently easily accessible from smartphones. Currently, there are five kinds of financial technology in Indonesia. There are investment, crowdfunding, microfinancing, peer-to-peer lending, and digital payment system. The digital payment system is the favourite and is usually used by the public. The popularity of fintech has a massive effect on financial behaviour. This research aims to understand the impact of financial technology, financial literacy, financial knowledge, locus of control, and income on financial management behaviour. This research is quantitive causality and implemented multiple linear regression data analysis techniques with IBM SPSS v.25 analysis software. The number sample 165 respondents using purposive sampling. An online questionnaire collects the responses. The respondents must meet the requirement of a fintech user living in Surabaya and aged between 15 to 65 years old. The output of the study does not show the impact of financial technology and locus of control on economic behaviour. However, the result has proven that financial literacy, financial knowledge, and income can impact financial management behaviour. This research can be a reference for fintech users to be wiser in managing finances and better at determining financial decisions.